2018
DOI: 10.1194/jlr.p080333
|View full text |Cite
|
Sign up to set email alerts
|

An exome-wide sequencing study of lipid response to high-fat meal and fenofibrate in Caucasians from the GOLDN cohort

Abstract: Our understanding of genetic influences on the response of lipids to specific interventions is limited. In this study, we sought to elucidate effects of rare genetic variants on lipid response to a high-fat meal challenge and fenofibrate (FFB) therapy in the Genetics of Lipid Lowering Drugs and Diet Network (GOLDN) cohort using an exome-wide sequencing-based association study. Our results showed that the rare coding variants in ITGA7, SIPA1L2, and CEP72 are significantly associated with fasting low-density lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…ITGA2 , an ITGA7 homolog, was reported to be associated with coronary atherosclerosis in the Chinese Han population (Wang Y. et al, 2010), drawing attention to the ITGA gene family in the cardiovascular context. We also observed associations between ITGA7 and LDL-C response to fenofibrate in another GOLDN study (Geng et al, 2018). In the conditional analysis after including LDL-C response to fenofibrate as a covariate, ITGA7 is still significantly associated with fasting TG ( P < 0.05).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…ITGA2 , an ITGA7 homolog, was reported to be associated with coronary atherosclerosis in the Chinese Han population (Wang Y. et al, 2010), drawing attention to the ITGA gene family in the cardiovascular context. We also observed associations between ITGA7 and LDL-C response to fenofibrate in another GOLDN study (Geng et al, 2018). In the conditional analysis after including LDL-C response to fenofibrate as a covariate, ITGA7 is still significantly associated with fasting TG ( P < 0.05).…”
Section: Discussionsupporting
confidence: 69%
“…The sequencing, genotyping, and quality control procedures were described in a prior study (Geng et al, 2018). Briefly, genomic DNA from peripheral blood nucleated cells was extracted using QIAmp 96 DNA Blood Kits (Qiagen, Hilden, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…This study included 422 GOLDN participants who were in the extreme tertiles of the lipid response to the high fat diet intervention and had lipidomics data available. The diet intervention has been described [20].…”
Section: Methodsmentioning
confidence: 99%
“…The next study to evaluate rare variants at the genome-wide level was performed with the GOLDN cohort [76]. Exome-wide sequencing was used to evaluate associations with fibrate response and interactions with high-fat diets.…”
Section: Candidate Gene Studiesmentioning
confidence: 99%
“…Irvin et al examined the impact of a high-fat diet on drug response in a candidate gene study but did not detect a direct gene-environment-environment interaction [94]. A previous study established that high-fat meals modify fibrate response [76,94], and genetic data from the GOLDN cohort was used to determine the impact of fibrate treatment on the association of APOE genotype differences and association with baseline lipids. The researchers found that while APOE was not directly associated with drug response (change in lipid levels), the association of overall lipid levels with APOE were conserved even after fibrate treatment, with slight mediation of effect sizes.…”
Section: Epistasis Modelingmentioning
confidence: 99%